Structural and magnetic characterization of the double perovskite Pb2FeMoO6. Issue 7 (28th January 2016) - Mezzadri, F.; Delmonte, D.; Orlandi, F.; Pernechele, C.; Calestani, G.; Solzi, M.; Lantieri, M.; Spina, G.; Cabassi, R.; Bolzoni, F.; Fittipaldi, M.; Merlini, M.; et al.
Abstract : Structural and magnetic characterization of Pb2 FeMoO6 reveals the central role played by nanometer-sized antiphase domains involved in the Fe/Mo cation ordering. Abstract : The chemical and physical properties of the double perovskite Pb2 FeMoO6 are systematically studied by means of structural and magnetic characterization. The compound crystallizes in the cubic Fm 3̄ m space group, with partial cation order involving iron and molybdenum at the perovskite B site. Structural and Mössbauer characterization points to the presence of nanometer-sized antiphase domains within the ordered matrix giving rise to two iron populations, characterized by different chemical environments, with the same weight but different valence (0.3 electrons) and inequivalent magnetic anisotropy. This structural feature deeply affects the properties of the compound: Mössbauer and EPR measurements show a high-temperature superparamagnetic-like behavior ascribed to weak magnetic interactions occurring between the antiphase domains and the rest of the sample. However, below 270 K ferrimagnetic ordering of the atomic moments is observed by neutron diffraction and SQUID magnetometry, with the onset of blocked long range magnetic interactions on the Mössbauer timescale involving both the antiphase domains and the ordered matrix below 230 K. The superparamagnetic-like behavior is ascribed to the presence of low anisotropy barriers, giving rise to an extremely thin hysteresis loop at 5 K, with a very small coercive field and remnant magnetization. The observed saturation magnetization of 1.75 μ B per f.u. is in agreement with the magnetic structure determined by neutron diffraction, with the two symmetry independent sites producing a ferrimagnetic resultant μ S = 1.59 μ B .